Effects of CO2 binary mixtures on pipeline performance for carbon capture and storage - Nor Khonisah, Daud (Elsevier Ltd, 2021)
Captured CO2 from the manufacturing industries and power generation sources are not pure and may contain usually some amount of impure components, which affect the flow dynamics of the CO2 in the pipelines. Major component of impure components includes N2, H2, H2S, O2, Ar etc., depending on the capture technology used for the removal of CO2 streams.To design efficient CO2 pipeline transportation systems, it is imperative to understand the effect of these impure components on the flow behaviour. The simulation of the effect of CO2 binary mixture on pipeline performance is carried out in this study. The steady-state flow in pipeline is described by a set of parabolic mass, momentum and energy conservation equations. To solve the set of equations subject to the boundary and the inlet conditions of the pipeline, the non-linear algebraic solver library DNSQE in Fortran is used to study the behaviour of 90 vol% CO2, and 10 vol% single impure component (N2, H2, H2S, O2and Ar). The phase diagram and pertinent fluid properties are calculated using the Peng-Robinson (PR) equation of state implemented in NIST Reference Fluid Thermodynamics and Transport Properties database program REFPROP. The results reveal that the bubble point curves were lifted up to higher pressures by impure components. The changes in the bubble point would affect the operating conditions of CO2pipeline. The presence of impure components also changed the properties of the flowing fluid. From the results, H2shows the most significant impact on the performance of CO2pipeline as the highest pressure drop by ca. 0.18 bar/km which has smaller density and greater flow velocity against other CO2streams. The results also show that Ar had the mildest effect followed by O2, N2and CO. In the case of H2S, the flow parameters are found to be nearly identical to those for pure CO2. The pressure drop for binary mixture contains H2S shows the same value with pure CO2 stream by ca. 0.13 bar/km.